The Triṣṭubh Hymn in the Bhagavadgītā - Ježić, Mislav (Array, 2009)
In the article on the Triṣ ṭ ubh Hymn in the Bhagavadgī tā the typology of textual repetitions distinguishing the compositional or continuity repetitions on the synchronical or syntagmatic axis and reinterpretative or duplication repetitions on the diachronical or paradigmatic axis has permitted to argue that not only the majority (as established already in Ježić 1979 and 1986), but very probably all the triṣ ṭ ubhs in the Gī tā originated from a religious hymn which must have been composed, partly on the basis of the epic layer of the Gī tā , as an independent poem before it was included in the Mahā bhā rata during the bhakti redation of the Gī tā . The article is followed by a tentative reconstruction of the order of stanzas in the hymn. With this analysis and reconstruction, the question about the Ur-Bhagavadgī tā inaugurated almost two centuries ago by Wilhelm von Humboldt has been hopefully finally answered.